Prevalence and sociodemographi aspects of dental anxiety to the dental treatment - Hilda Elia Rodriguez Chala; Ailyn Pérez Sorondo; Marbelis Quiñones Plata; Maihanel Lorenzo Ramos (Editorial Ciencias Médicas, 2017)
Introduction: dental anxiety is a phenomenon that affects the oral health status, hindering both patient management and the subsequent treatment adherence. In Cuba this psychological disorder has been poorly known in the dental setting, therefore, a great knowledge on the aspects related to its prevalence and sociodemographic characteristics is of vital importance as a starting point for further researches and for drawing of strategies in controlling this phenomenon. Objective: to make a literature review on prevalence and sociodemographic aspects of dental anxiety. Methods: a review study was conducted, which included the literature published from 2010 to June 2015. Eighty one papers were found from which some that addressed anxiety in individuals with specific characteristics or some type of disease were excluded and 53 were selected to be reviewed and finally 42 were considered at the author´s criteria. Data analysis and integration: the prevalence of dental anxiety manifests generally in children and adults; moderate to severe levels are evident in most studies with significant values. Age and sex are the most associated variables, it tends to decrease with increasing age, and women express anxiety more freely. Conclusions: dental anxiety is a psychological phenomenon affecting the world population, with increasing tendency in women and young people. The educational level and the marital status show ambivalent criteria with respect to this disorder.